THE PORTRAYAL OF PSYCHOLOGICAL OPPRESSION TOWARD SEYMOUR FLEMING AS FEMALE CHARACTER IN THE SCANDALOUS LADY W FILM - Much. Eko Wahyu Rianto; Singgih Daru Kuncara; Chris Asanti (Ilmu Budaya: Jurnal Bahasa, Sastra, Seni, dan Budaya, 2022)
This research is aimed to portray the psychological oppression in the The Scandalous Lady W film, which is experienced by Seymour Fleming as the main woman character. This research used a theory of Psychological Oppression by Sanda Lee Bartky. The method that had been used by the researcher was the qualitative method. As the result, this research shows that there are three components of psychological oppression portrayed in the film. First, stereotyping which shows that all women who lived in that era were considered as property to their husband. Second, cultural domination which is shown the domination of men culture in life with their authorities and positions. Lastly, sexual objectification which portrayed by Seymour Fleming as the main woman character in this film was sexually objected by her husband. She was oppressed for having an intimate relationship through twenty-seven men chosen by her husband during their marriage life.